Unveiling Indigenous Health Knowledge through Folk Songs: Prau Layar, Padhang Wulan, Suwe Ora Jamu, Kodok Ngorek - Nurislaminingsih, Rizki; Rochwulaningsih, Yety (Journal of Maritime Studies and National Integration, 2023)
Indonesia's territory, which consists of land and sea, is a positive side that supports aspects of public health. The sea can be used as a vacation spot (mental health) while the land can be used to plant herbal plants (body health). Community knowledge about these health benefits is shared in folklore activities, in the form of folk songs. People create songs to store and share knowledge about health. The folk songs are Prau Layar, Padhang Wulan, Suwe Ora Jamu, and Kodok Ngorek. This study aims to explore indigenous knowledge in those folk songs. The results showed that the knowledge contained in folk songs was mental health (the importance of picnics at the sea, playing and joking with friends), body health (taking naps), and the names of ingredients for making jamu (traditional health drinks). The conclusion is that the indigenous knowledge contained in folk songs is mental health, body health, and herbs for making traditional health drinks. The findings in this study is that cassava leaves and sweet potato leaves have potential as natural skincare ingredients.